Complex of Cyclosporins Produced by Tolypocladium inflatum Isolated from Soil Sample of Buryatiya - M. V. Bibikova; T. A. Darkhanova; I. A. Spiridonova; A. N. Danilenko; A. V. Katlinsky (Антибиотики и Химиотерапия, 2020)
A micromycete culture was isolated from a soil sample of Buryatiya and identified as Tolypocladium inflatum No. 2. The culture was shown to produce a complex of cyclosporins ofunusual component structure: the content of cyclosporin A (55—60%) was the same as that in the substances produced by the majority of the described cultures, the content of cyclosporin B was much higher (about 40%) and the content of cyclosporin C was relatively low (about 3%). An appreciable content of cyclosporin (Leu4)Cs (3%) proved to be of interest.